Intangible Assets and Financial Performance of Nigeria’s Deposit Money Banks - Olaoye, Samuel Adebayo; Akingbade, Adedoyin Oluwapelumi; Okewale, Joel Adeniyi (NIU Journal of Humanities, 2020)
One of the measures of organisational success is its financial performance. In this study, the relationship between intangible assets and financial returns of Nigeria’s deposit money banks (DMOs) was investigated. Secondary data from annual reports and account of the selected DMOs were collected and analysed using panel ordinary least square regression, descriptive statistics, correlation analysis and Hausman test. Results reveal a positive but insignificant relationship between intangible assets and profitability of Nigeria’s deposit money banks. It is therefore recommended that organisation should invest significantly in intangible assets in order to boost profitability. Keywords: Intangible Asset, Profitability, IAS 38, IFRS, Goodwill